Lipoprotein receptors and a Disabled family cytoplasmic adaptor protein regulate EGL-17/FGF export in C. elegans - Kamikura, Darren M. (Cold Spring Harbor Laboratory Press, 2003)
Growth factors and morphogens need to be secreted to act on distant cells during development and in response to injury. Here, we report evidence that efficient export of a fibroblast growth factor (FGF), EGL-17, from the Caenorhabditis elegans developing vulva requires the lipoprotein receptor-related proteins Ce-LRP-1 and Ce-LRP-2 and a cytoplasmic adaptor protein, Ce-DAB-1 (Disabled). Lipoprotein receptors are transmembrane proteins best known for their roles in endocytosis. Ce-LRP-1 and Ce-LRP-2 possess a conserved intraluminal domain that can bind to EGL-17, as well as a cytosolic FXNPXY motif that can bind to Ce-DAB-1. Ce-DAB-1 contains signals that confer subcellular localization to Golgi-proximal vesicles. These results suggest a model in which Ce-DAB-1 coordinates selection of receptors and cargo, including EGL-17, for transport through the secretory pathway.